1985
DOI: 10.1111/j.1471-4159.1985.tb05524.x
|View full text |Cite
|
Sign up to set email alerts
|

[3H]Threo‐(±)‐Methylphenidate Binding to 3,4‐Dihydroxyphenylethylamine Uptake Sites in Corpus Striatum: Correlation with the Stimulant Properties of Ritalinic Acid Esters

Abstract: Saturable and stereoselective binding sites for [3H]threo-(+/-)-methylphenidate were characterized in rat brain membranes. The highest density of [3H]threo-(+/-)-methylphenidate binding sites was found in the synaptosomal fraction of corpus striatum. Scatchard analysis revealed a single class of noninteracting binding sites with an apparent dissociation constant (KD) of 235 nM and a maximum number of binding sites (Bmax) of 13.4 pmol/mg protein. Saturable, high-affinity binding of [3H]threo-(+/-)-methylphenida… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
84
0

Year Published

1997
1997
2018
2018

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 138 publications
(90 citation statements)
references
References 19 publications
6
84
0
Order By: Relevance
“…Our comparative PET studies demonstrate the neurochemical specificity of d-threo-MP in vivo, supporting the prevailing view that the stimulant effects of MP and related drugs are related more consistently to their inhibitory actions on the dopamine transporter than other neurotransmitter transporters; however, l-threo-MP only contributes to non-specific binding. These results are consistent with a number of behavior, in vitro and ex-vivo studies (Ferris et al 1972;Schweri et al 1985;Patrick et al 1987;Eckerman et al 1991;Aoyama et al 1994). Our microdialysis studies in free moving rats, which allow us directly to measure the effect of a drug on extracellular striatal dopamine in the brain, further demonstrate that pharmacological specificity of MP resides entirely in the d-threo isomer and the binding of l-isomer is mostly non-specific.…”
Section: Microdialysis Studiessupporting
confidence: 80%
See 1 more Smart Citation
“…Our comparative PET studies demonstrate the neurochemical specificity of d-threo-MP in vivo, supporting the prevailing view that the stimulant effects of MP and related drugs are related more consistently to their inhibitory actions on the dopamine transporter than other neurotransmitter transporters; however, l-threo-MP only contributes to non-specific binding. These results are consistent with a number of behavior, in vitro and ex-vivo studies (Ferris et al 1972;Schweri et al 1985;Patrick et al 1987;Eckerman et al 1991;Aoyama et al 1994). Our microdialysis studies in free moving rats, which allow us directly to measure the effect of a drug on extracellular striatal dopamine in the brain, further demonstrate that pharmacological specificity of MP resides entirely in the d-threo isomer and the binding of l-isomer is mostly non-specific.…”
Section: Microdialysis Studiessupporting
confidence: 80%
“…It is this stimulation which is believed to regulate attention and impulsivity of ADHD children. However, it has been shown that d-threo-MP is more potent in the induction of locomotor activity and has a higher affinity for the dopamine transporter than l-threo-MP (Barkely 1977;Schweri et al 1985;Patrick et al 1987;Ritz et al 1987;Pan et al 1994). An important concern is, "should we use racemic drug or single enantiomer?"…”
Section: Introductionmentioning
confidence: 99%
“…One important difference between methylphenidate and cocaine/amphetamine is the low affinity of methylphenidate for the serotonin transporter (Schweri et al, 1985;Gatley et al, 1996). Indeed, in contrast to cocaine and amphetamine, methylphenidate does not produce increased extracellular levels of serotonin (Kuczenski and Segal, 1997;Kankaanpaa et al, 2002).…”
Section: Methylphenidate-induced Gene Regulation M Yano and H Steinermentioning
confidence: 99%
“…Methylphenidate (Ritalin) is a psychostimulant that is widely used in the treatment of attention-deficit hyperactivity disorder in adolescents and adults, and is also diverted for recreational purposes (Kollins et al, 2001;Swanson and Volkow, 2003). Methylphenidate binds and inhibits the dopamine transporter (Schweri et al, 1985;Gatley et al, 1996) and produces dopamine overflow in the striatum (Hurd and Ungerstedt, 1989;Butcher et al, 1991;Kuczenski and Segal, 1997;Gerasimov et al, 2000;Volkow et al, 2001). In addition, this psychostimulant inhibits norepinephrine reuptake (Kuczenski and Segal, 1997) and affects vesicular monoamine transport (Sandoval et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…The twenty minute local tissue perfusions of drugs induced a concentration-dependent i n c r e a s e i n D A o v e r f l o w f o l l o w e d b y a 6 0 m i n u t e t i m e p e r i o d t o r e t u r n t o b a s e l i n e supporting the DAT and DA uptake blocking effects of the tested stimulants (Wise and Hoffman 1992;Sulzer et al 1993;Schweri et al 1985). The resulting DA levels, at the highest concentration of drug, were similar to previous microdialysis measures of ~150 nM (Seeman and Madras 2002).…”
Section: Reverse Microdialysis Of Stimulants In the Rat Striatum: Resmentioning
confidence: 99%